In situ assessment of statins’ effect on autophagic activity in zebrafish larvae cardiomyocytes - Zhang, Jie; Zuo, Zhi; Li, Jianxuan; Wang, Ying; Huang, Jia; Xu, Lili; Jin, Kejia; Lu, Hao; Dai, Yuxiang (Frontiers in Cardiovascular Medicine, 2022)
Improving the survival rate of cardiomyocytes is the key point to treat most of the heart diseases, and targeting autophagy is a potential advanced therapeutic approach. Monitoring autophagic activity in cardiomyocytes in situ will be useful for studying autophagy-related heart disease and screening autophagy-modulating drugs. Zebrafish, Danio rerio, has been proven as an animal model for studying heart diseases in situ. Taken the advantage of zebrafish, especially the imaging of intact animals, here we generated two stable transgenic zebrafish lines that specifically expressed EGFP-map1lc3b or mRFP-EGFP-map1lc3b in cardiomyocytes under the promoter of myosin light chain 7. We first used a few known autophagy-modulating drugs to confirm their usefulness. By quantifying the density of autophagosomes and autolysosomes, autophagy inducers and inhibitors showed their regulatory functions, which were consistent with previous studies. With the two lines, we then found a significant increase in the density of autophagosomes but not autolysosomes in zebrafish cardiomyocytes at the early developmental stages, indicating the involvement of autophagy in early heart development. To prove their applicability, we also tested five clinical statins by the two lines. And we found that statins did not change the density of autophagosomes but reduced the density of autolysosomes in cardiomyocytes, implying their regulation in autophagic flux. Our study provides novel animal models for monitoring autophagic activity in cardiomyocytes in situ, which could be used to study autophagy-related cardiomyopathy and drug screening.